2019
DOI: 10.3390/su11102780
|View full text |Cite
|
Sign up to set email alerts
|

Participant Outcomes of Biodiversity Citizen Science Projects: A Systematic Literature Review

Abstract: Citizen science is becoming increasingly popular as a format in environmental and sustainability education. Citizen science not only allows researchers to gather large amounts of biodiversity-related data, it also has the potential to engage the public in biodiversity research. Numerous citizen science projects have emerged that assume that participation in the project affects participants’ knowledge, attitudes, and behavior. We investigated what evidence really exists about the outcomes of biodiversity citize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
117
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(129 citation statements)
references
References 61 publications
10
117
0
2
Order By: Relevance
“…In addition to its increasing popularity in scientific research, CS has gained consideration in science and environmental education research [36,37]. Peter et al [38] reviewed publications on the educational impacts of biodiversity-related CS projects. They conclude that CS is a suitable approach for biodiversity education.…”
Section: Futureforest-engaging Students In Biodiversity Conservationmentioning
confidence: 99%
“…In addition to its increasing popularity in scientific research, CS has gained consideration in science and environmental education research [36,37]. Peter et al [38] reviewed publications on the educational impacts of biodiversity-related CS projects. They conclude that CS is a suitable approach for biodiversity education.…”
Section: Futureforest-engaging Students In Biodiversity Conservationmentioning
confidence: 99%
“…Knowledge of threatening processes to wildlife and of general conservation issues can be a precursor to pro‐environmental attitudes, behaviour, and engagement with conservation (Hines et al., 1987). Several citizen science projects have increased their participants' knowledge on the subject investigated (Branchini et al., 2015; Haywood et al., 2016; Peter et al., 2019; Schuttler et al., 2018). Usually, people who volunteer to participate in citizen science are already interested in the topic, want to learn more about it, and want to contribute to the field (Van Den Geoghegan et al., 2016; Lewandowski & Oberhauser, 2017; Berg et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, pro‐environmental behaviours may require skills (that are additional to knowledge) to address environmental problems (Hines et al., 1987; Wiernik et al., 2018). Citizen science can improve participants' skills (Peter et al., 2019). For example, volunteers in Australia reported learning technical skills for bush restoration and sustainable living throughout their time as participants in environmental projects or in environmental groups (Measham & Barnett, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…SLR is a literature review that is firmly attached to a set of scientific methods explicitly with the aim of avoiding systematic or biased errors [46]. This study uses several stages as suggested by Peter [47] about preferred reporting items for systematic reviews and meta-analysis or PRISMA. These stages are identification, screening, eligibility, and inclusion.…”
Section: Methodsmentioning
confidence: 99%